Design and off-design performance analysis of a liquid carbon dioxide energy storage system integrated with low-grade heat source. (25th June 2023) - Xu, Wenpan; Zhao, Pan; Liu, Aijie; Wu, Wenze; Wang, Jiangfeng
Graphical abstract: Highlights: A liquid supercritical CO2 energy storage system is proposed. The influence of pseudo-critical points on system are investigated. The preliminary geometric parameters of system components are designed. The system design and off-design performances are executed. Abstract: Nowadays, developing the renewable energy has become the worldwide consensus. Nevertheless, the intermittency and volatility of renewable electricity bring great challenges to the stability of the power grid. Liquid carbon dioxide energy storage is recognized as one of the most promising technologies to overcome these difficulties. In this paper, a liquid carbon dioxide energy storage system integrated with the low-grade heat source is proposed. Based on the preliminary geometric parameters of system components, investigations on the system design and off-design performances are carried out. Results of parametric analysis indicate that the pseudo-critical point corresponding to 8 MPa is recommended as the design point for compressor inlet, and the minimum value of LCOE could reach 9.49 cents/kWh. Under design conditions, the system exergy efficiency reaches 48.42% and the roundtrip efficiency is 63.60%. Moreover, 10.70 cents/kWh of the per unit generation cost is advantageous in the large-scale energy storage systems. With the variations of input power (70%∼120%) and output power level (50%∼100%), the surplus water ratio could reach 23.63% at 50% load level, while the variation range of exergy efficiency is 15.56%∼48.42%. Meanwhile, the roundtrip efficiency varies from 22.16% to 63.60% under off-design conditions, and the maximum value is achieved at the design point. All the results identify the feasibility of the integrated energy storage system.